Fish Oil Reduces Hepatic Injury by Maintaining Normal Intestinal Permeability and Microbiota in Chronic Ethanol-Fed Rats. (10th April 2016) - Chen, Jiun-Rong; Chen, Ya-Ling; Peng, Hsiang-Chi; Lu, Yu-An; Chuang, Hsiao-Li; Chang, Hsiao-Yun; Wang, Hsiao-Yun; Su, Yu-Ju; Yang, Suh-Ching
Abstract : The aim of this study was to investigate the ameliorative effects of fish oil on hepatic injury in ethanol-fed rats based on the intestinal permeability and microbiota. Rats were assigned to 6 groups and fed either a control diet or an ethanol diet such as C (control), CF25 (control with 25% fish oil), CF57 (control with 57% fish oil), E (ethanol), EF25 (ethanol with 25% fish oil), and EF57 (ethanol with 57% fish oil) groups. Rats were sacrificed at the end of 8 weeks. Plasma aspartate aminotransferase (AST) and aminotransferase (ALT) activities, hepatic cytokines, and plasma endotoxin levels were significantly higher in the E group. In addition, hepatic histopathological analysis scores in the E group were significantly elevated. Rats in the E group also showed increased intestinal permeability and decreased numbers of fecal Bifidobacterium . However, plasma AST and ALT activities and hepatic cytokine levels were significantly lower in the EF25 and EF57 groups. Histological changes and intestinal permeability were also improved in the EF25 and EF57 groups. The fecal Escherichia coli numbers were significantly lower, but fecal Bifidobacterium numbers were significantly higher in the EF25 and EF57 groups.